Geospatial Intelligence (GEOINT)-Based Cyber Warfare Exposure Index (CWEI) Mapping of Indonesia's Strategic Infrastructure - Adityayuda, Anugrah; Supriyadi, Asep Adang; Arief, Syachrul (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2026)
The increasing integration of digital systems into critical infrastructure has transformed cyber warfare into a systemic national security risk with strong spatial characteristics. In Indonesia, rapid digitalization and uneven infrastructure development have expanded the cyber-attack surface, while existing studies remain largely qualitative or rely on aggregated national indices that fail to capture subnational exposure patterns. This study addresses this gap by developing a Cyber Warfare Exposure Index (CWEI) based on Geospatial Intelligence (GEOINT) to assess provincial-level exposure across Indonesia. The index integrates seven indicators, energy, transportation, telecommunications, government facilities, internet penetration, night-time light intensity, and urbanization, derived from open-source geospatial data and official statistics. All indicators were normalized using min–max scaling and aggregated through equal weighting, with robustness tested using Principal Component Analysis (PCA), Pearson correlation, and One-at-a-Time sensitivity analysis. Results reveal strong spatial disparities in cyber warfare exposure, with CWEI values ranging from 0.019 to 0.746. DKI Jakarta exhibits the highest exposure (CWEI = 0.746), followed by West Java (0.573) and Central Java (0.564), while several eastern provinces fall into the very low exposure category. The equal-weight and PCA-based indices show near-perfect agreement (R² = 0.997; r = 0.998), confirming high methodological robustness. Global Moran's I (0.689; p < 0.001) indicates significant positive spatial clustering of exposure. These findings demonstrate that cyber warfare exposure in Indonesia is highly concentrated and spatially structured, underscoring the need for regionally prioritized, risk-based cyber defense strategies.